Pemberdayaan Masyarakat Nelayan Melalui Inkubator Bisnis Dalam Mengolah Hasil Laut - Lioni Asmirelda; Yoseph Felix Rahardjo; Niki Moktika Dwi Megawati; Yokhebed Rajagukguk; Endah Setya Octaviani; Hanny Oktaria (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2020)
This community service activity aims to improve the economy of the fishing communities of Kampung Tua Nongsa through entrepreneurial consulting and mentoring training and business incubators. The purpose of carrying out entrepreneurial mentoring activities to reduce this problem, namely: 1) Provide entrepreneurial assistance and business incubators, 2) Provide skills in managing fish and gonggong raw materials into innovative and economic value products, 3) Provide additional skills training such as managing financial reports, 4) The target of this activity is the mothers of the fishing community Kampung Tua Teluk Mata Ikan Nongsa located on the coast. The method of implementing entrepreneurial training activities will be made with the pre and post test methods. The output of this activity are: 1) Create new products from materials found in Kampung Tua Nongsa, 2) Create a community that is able to identify business opportunities, make business plans, perform packing procedures according to existing standards, and conduct marketing strategies through partners and other strategies and simple financial report making, 3) Development of skills for students to carry out the third tri darma of higher education, namely community service.